Relationship between Advanced Glycation End-products, Serum Carnosinase-1 and Diabetic Nephropathy and Diabetic Retinopathya: Advanced Glycation End-products, Carnosinase-1 and Diabetic Microangiopathy - Rong, Yu (Journal of Medical Biochemistry, 2025)
Introduction: This article analyzed the relationship between serum advanced glycation end-products (AGEs), carnosinase-1 (CN-1) and diabetic nephropathy (DN) and diabetic retinopathy (DR). Material and Method: 150 patients with type 2 diabetes mellitus (DM2) were grouped: DN and non-DN, DR and non-DR groups. Fasting venous blood was collected, and serum levels of AGEs and CN-1 were detected. Pearson’s correlation (PC) test was adopted for analyzing their correlation with DN and DR, and multivariate Logistic regression (MLR) analysis was adopted. Result: There were 48 DN cases, 102 non-DN cases, 20 DR cases, and 130 non-DR cases in 150 patients with DM2. As against the non-DN group, the serum levels of AGEs and CN-1 in the subjects with DN were markedly increased. As against the non-DR group, the serum levels of AGEs and CN-1 in the subjects with DR were also markedly increased. The results of correlation analysis revealed that the levels of serum AGEs and CN-1 were positively correlated with the occurrence of DN and DR. Serum AGEs and CN-1 levels were independent risk factors (IRF) for DN and DR (all P
Keywords: AGEs; CN-1; DN; DR